Clinical, genetic, and cellular analysis of 49 osteopetrotic patients: implications for diagnosis and treatment. Issue 4 (23rd August 2005) - Del Fattore, A; Peruzzi, B; Rucci, N; Recchia, I; Cappariello, A; Longo, M; Fortunati, D; Ballanti, P; Iacobini, M; Luciani, M; Devito, R; Pinto, R; et al.
Abstract : Background: Osteopetrosis, a genetic disease characterised by osteoclast failure, is classified into three forms: infantile malignant autosomal recessive osteopetrosis (ARO), intermediate autosomal recessive osteopetrosis (IRO), and autosomal dominant osteopetrosis (ADO). Methods: We studied 49 patients, 21 with ARO, one with IRO, and 27 with type II ADO (ADO II). Results: Most ARO patients bore known or novel (one case) ATP6i (TCIRG1) gene mutations. Six ADO II patients had no mutations in ClCN7, the only so far recognised gene implicated, suggesting involvement of yet unknown genes. Identical ClCN7 mutations produced differing phenotypes with variable degrees of severity. In ADO II, serum tartrate resistant acid phosphatase was always elevated. Bone alkaline phosphatase (BALP) was generally low, but osteocalcin was high, suggesting perturbed osteoblast differentiation or function. In contrast, BALP was high in ARO patients. Elevated osteoclast surface/bone surface was noted in biopsies from most ARO patients. Cases with high osteoclasts also showed increased osteoblast surface/bone surface. ARO osteoclasts were morphologically normal, with unaltered formation rates, intracellular pH handling, and response to acidification. Their resorption activity was greatly reduced, but not abolished. In control osteoclasts, all resorption activity was abolished by combined inhibition of proton pumping and sodium/proton antiport. Conclusions: These findings provide a rationale for novel therapies targeting pH handling mechanisms in osteoclasts and their microenvironment.